Analisis Determinan Persepsi Masyarakat di Lingkungan Sekitar Industri Farmasi PT.X Kota Palembang - Tuti'ul Amrina; Hilda Zulkifli; Muhammad Faizal (Politeknik Kesehatan Tanjung Karang, 2019)
The activities of the pharmaceutical industry are located bordering to the settlement of the negative impact on public health. This research aims to analyze the perception of the public, especially related to the nearest public health pharmaceutical industry PT.X location in the Village 5 Ilir, District II East Ilir Palembang. This study was conducted in September 2018. The population of this study was 600 households. in addition, the researcher used random sampling. There were 126 sample households which were the people who live in the ring-I industry. The study used a quantitative method by cross-sectional design. the Data collection instrument was a questionnaire, they are conducted based on the concept of health belief models, interviews and observations, the data were analyzed by using multiple logistic regression. The results showed that the perception of the public (56,3%) of the public health-related industries categorized as good. Characteristics of the community are mostly aged >43 years (51.6%), highly educated (>D3) of 53,2%, including a long stay at the old category (51,6%), good knowledge of (74,6%), and has the highest employment as self-employed (43,0%) as well as good health condition of (62,7%). The results of multiple logistic regression showed that the variable length of stay (OR=0,20); variable educational level (OR=0,30); knowledge variable (OR=4.=,81); public health (OR=3,89) affect the public perception of the pharmaceutical industry. 6%), and has the highest employment as self-employed (43,0%) as well as the good health condition of (62,7%). The results of multiple logistic regression showed that the variable length of stay (OR=0,20); variable educational level (OR=0,30); knowledge variable (OR=4,81); public health (OR=3,89) affect the public perception of the pharmaceutical industry.